Morphological Change by Overexpression of D385A Dominant Negative Presenilin 1 in Human Neuroblastoma SH-SY5Y Cells - Daiju Tsuchiya; Yoshihisa Kitamura; Kazuyuki Takata; Takashi Taniguchi; Kengo Uemura; Hiroaki Miki; Tadaomi Takenawa; Shun Shimohama (Elsevier, 2006)
Presenilin 1 (PS1) is a multifunctional protein, and its mutations are highly related to familial Alzheimer's disease (AD). In this study, we examined the effects of PS1 overexpression on neuronal morphology using SH-SY5Y cells. Overexpression of dominant-negative D385A PS1 induced morphological change and impairment of neurite formation, while those of wild-type and pathogenic P117L mutant PS1 did not change cellular morphology compared with native cells. Moreover, filopodium-formation-related proteins were decreased only in cells overexpressing D385A PS1. Therefore, PS1 may be involved in neuritogenesis and morphological change in SH-SY5Y cells, and P117L mutation may linked to AD by different mechanisms. Keywords:: presenilin 1, SH-SY5Y cell, neuritogenesis